2020
DOI: 10.1159/000507853
|View full text |Cite
|
Sign up to set email alerts
|

Adult Ocular Myasthenia Gravis Conversion: A Single-Center Retrospective Analysis in China

Abstract: Introduction: The conversion rate from ocular myasthenia gravis (OMG) to generalized myasthenia gravis (GMG) was reported to be much lower in Asian population since most OMG patients are juvenile onset. However, the exact conversion rate for adult-onset OMG to GMG is still unknown. Objective: We aimed to delineate the conversion rate and risk factors for adult patients with ocular onset to GMG. Methods: Adult myasthenia gravis (MG) patients with ocular onset (age > 18 years) were retrospectively reviewed. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Our study found that patients with adult-onset OMG were more likely to develop generalization than those with the juvenile-onset form of this disease; moreover, those with late-onset OMG had a higher risk of generalization. This finding is consistent with results from previous studies [ 8 , 13 , 14 , 20 , 21 ]. Wang et al reported the group with secondary generalization in their study comprised more late-onset patients [ 8 ].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Our study found that patients with adult-onset OMG were more likely to develop generalization than those with the juvenile-onset form of this disease; moreover, those with late-onset OMG had a higher risk of generalization. This finding is consistent with results from previous studies [ 8 , 13 , 14 , 20 , 21 ]. Wang et al reported the group with secondary generalization in their study comprised more late-onset patients [ 8 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our study found that patients with adultonset OMG were more likely to develop generalization than those with the juvenile-onset [13]. The reported incidence and prevalence of late-onset MG (age of onset C 50 years) have steadily increased over the last decades [22].…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations